Legal Guarantees for the Protection of the Labor Rights of Persons with Disabilities in Ukraine - Трюхан, Оксана Анатоліївна; Трюхан, О. А.; Трюхан, Оксана Анатольевна; Triukhan, Oksana A.; Чумаченко, Інна Євгенівна; Чумаченко, І. Є.; Чумаченко, Инна Евгениевна; Chumachenko, Inna Ye.; Занько, Олена Валентинівна; Занько, О. В.; Занько, Елена Валентиновна; Zanko, Olena V.; et al. (Canadian Center of Science and Education, 2020)
The content of universal and European regional international instruments on protection of labor rights of persons with disabilities is analyzed in the paper. The conclusion is made that Ukraine should take into account the positive foreign experience of the leading countries in the field of state policy of support for persons with disabilities and its implementation. It is justified that the world experience in the field of employment for persons with disabilities will facilitate the practical implementation not only of government programs but also of measures to protect the interests of persons with disabilities. A number of scholarly publications on the subject have been investigated, containing suggestions by scientists to improve promising labor law regarding the manifestations of discrimination on the basis of disability in the field of work. Some theoretically sound recommendations for improving the legal regulation of the protection of the labor rights of persons with disabilities and ensuring that they fulfill their responsibilities were developed. General conclusions have been drawn that the problem of the legal mechanism for the protection of the labor rights of persons with disabilities needs reforming and improvement. Some proposals for improving the legal regulation in this field were given.

У статті проаналізовано зміст універсальних та європейських регіональних міжнародних документів про захист трудових прав інвалідів. Зроблено висновок про те, що Україні слід враховувати позитивний зарубіжний досвід провідних країн у галузі державної політики підтримки інвалідів та її реалізації. Виправдано, що світовий досвід у галузі працевлаштування людей з інвалідністю сприятиме практичному впровадженню не лише державних програм, а й заходів щодо захисту інтересів інвалідів. Досліджено низку наукових публікацій на цю тему, що містять пропозиції вчених щодо вдосконалення перспективного трудового законодавства щодо проявів дискримінації за ознакою інвалідності у сфері праці. Розроблено кілька теоретично обгрунтованих рекомендацій щодо вдосконалення правового регулювання захисту трудових прав інвалідів та забезпечення їх обов'язкового виконання. Зроблено загальні висновки про те, що проблема правового механізму захисту трудових прав інвалідів потребує реформування та вдосконалення. Дано кілька пропозицій щодо вдосконалення правового регулювання у цій галузі.

В статье проанализировано содержание универсальных и европейских региональных международных документов о защите трудовых прав инвалидов. Сделан вывод о том, что Украине следует учитывать положительный зарубежный опыт ведущих стран в области государственной политики поддержки инвалидов и ее реализации. Оправданно, что мировой опыт в области трудоустройства людей с инвалидностью будет способствовать практическому внедрению не только государственных программ, но и мер по защите интересов инвалидов. Исследован ряд научных публикаций на эту тему, содержащих предложения ученых по совершенствованию перспективного трудового законодательства в отношении проявлений дискриминации по признаку инвалидности в сфере труда. Разработано несколько теоретически обоснованных рекомендаций по совершенствованию правового регулирования защиты трудовых прав инвалидов и обеспечения их обязательного выполнения. Сделано общие выводы о том, что проблема правового механизма защиты трудовых прав инвалидов нуждается в реформировании и совершенствовании. Дано несколько предложений по совершенствованию правового регулирования в этой области.
Triukhan О. Legal Guarantees for the Protection of the Labor Rights of Persons with Disabilities in Ukraine / O. Triukhan, I. Chumachenko, O. Zanko, А. Hodovaniuk, V. Formaniuk // Journal of Politics and Law. – V. 13 (2). – Canadian Center of Science and Education, 2020. – Р. 164-174.
Keywords: persons with disabilities; labor rights; employment; guarantees; discrimination; protection; інваліди; трудові права; працевлаштування; гарантії; дискримінація; захист; инвалиды; трудовые права; трудоустройство; гарантии; дискриминация; защита; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Labour law